Leadership education to support person-centred health and social care: A scoping review of empirical literature - Qarin Lood; Ewa Carlsson Lalloo; Jana Bergholtz; Emmelie Barenfeld (PLoS ONE, 2026)
The purpose of this scoping review was to map evidence on leadership education to support person-centred care. Specifically, the review aimed to identify the key content of such education, the educational methods used, the reported results, and gaps in the existing literature. The review was conducted using the Joanna Briggs Institute methodology for scoping reviews and reported in accordance with PRISMA-ScR guidelines. Peer-reviewed empirical literature on leadership education for people with leadership roles in health and social were included, without restrictions on publication year or study design. Qualitative, quantitative, and mixed-methods designs were eligible. Educational methods were summarised descriptively, and education content and results were iteratively synthesised and categorised. Methodological quality was not formally assessed, consistent with scoping review methodology. Of 2548 identified records, 22 publications met the eligibility criteria. Leadership education interventions were predominantly conducted in Northern Europe and mainly targeted registered nurses in leadership roles. Educational content commonly addressed leadership theories and styles, person-centredness, and facilitation skills. Educational methods were largely based on longitudinal, work-based learning approaches, and reported results primarily reflected perceived improvements in leadership practices, workplace culture, and care practice outcomes. However, outcomes were largely self-reported, context-specific, and seldom assessed using standardised or comparative measures. Interpretation of the findings is limited by the small number of publications, the predominance of qualitative and non-comparative designs, and the narrow geographical and professional focus of the evidence. These limitations restrict conclusions regarding effectiveness, generalisability, scalability, and sustained system-level impact. Despite these limitations, the findings suggest that leadership education may support leadership practices and care improvement. The review identifies substantial gaps in the global evidence base, highlighting the need for more diverse, theory-informed, and rigorously evaluated leadership education that engages multiple professional groups, incorporates patient and relative perspectives, and examines implementation and transferability across varied health and social care contexts.